Programs and services for older people in fitness centers in Seville - Jerónimo García Fernández; Jesús Fernández Gavira (FEADEF, 2010)
The practice of physical activity by older people is increasingly becoming very usual within this population. Therefore, the sports facilities, are offering specific programs and activities to improve the quality of life for this population. One of the places where these activities are offered, are the private fitness centers (PFC), where nowadays is getting more frequent to find seniors doing exercises in the latest generation apparatus and dealing with modern equipment.Our study reflects the reality of 45 PFC of a Spanish city, Seville, in relation to specific fees and activities offered for seniors at these centers. Similarly, it shows the status of this offer in relation to the census districts of Seville. The research found out that most of the centers analyzed did not have a specific program with activities for seniors.